Five dimensions of brand personality traits in sport. Issue 4 (August 2016) - Kang, Chanho; Bennett, Gregg; Welty Peachey, Jon
Highlights: The lexical approach is a theoretical basis for studying sport brand personality. The HEXACO model for identifying brand personality dimensions is explored. The five identified factors resemble the structure of human personality models. Abstract: The first purpose of this study was to elaborate upon existing critiques and return to the fundamental brand personality concept by reexamining personality trait theory (i.e., lexical approach) and the sport brand personality literature. Based on a conceptualisation of sport brand personality, the second purpose was to develop an instrument for measuring brand personality in sport based on the restricted definition that excludes non-human personality traits. We adopted the lexical approach in an effort to explore the application of the HEXACO model for obtaining a set of representative personality traits ( N  = 36) both applicable and relevant to sport brands. For the purpose of this study, a sport brand × subject structure was utilised to find major sport brand personality dimensions. As a representative brand in sport, the National Football League was selected. Two data sets were collected from college students. The 36 sport brand personality traits were submitted to a principal axis factor analysis on the first data set ( N  = 196). The analysis identified five factors (i.e., Agreeableness, Extraversion/Emotionality, Openness, Conscientiousness, and Honesty) that closely resemble the structure of human personality models. A Confirmatory Factor Analysis confirmed that the newly developed five-factor model has an acceptable fit to the second data set ( N  = 155). This study identified that the lexical approach can provide a conceptual and methodological foundation when developing brand personality instruments.